2015
DOI: 10.3847/2041-8205/816/1/l8
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Power-Law Energy Spectra in Collisionless Relativistic Magnetic Reconnection in Pair Plasmas

Abstract: Using two-dimensional particle-in-cell simulations, we characterize the energy spectra of particles accelerated by relativistic magnetic reconnection (without guide field) in collisionless electron-positron plasmas, for a wide range of upstream magnetizations σ and system sizes L. The particle spectra are well-represented by a power law γ −α , with a combination of exponential and super-exponential high-energy cutoffs, proportional to σ and L, respectively. For large L and σ, the power-law index α approaches a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
313
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 269 publications
(384 citation statements)
references
References 51 publications
67
313
2
2
Order By: Relevance
“…On the other hand, it has been suggested that the development of a power law requires a loss mechanism in addition to an energy drive 22 . However, several recent simulations suggest that power-law spectra may still develop in the absence of a loss mechanism 26,27,36,55 . The set of conditions under which power-law spectra form in kinetic reconnection simulations remains an open issue.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been suggested that the development of a power law requires a loss mechanism in addition to an energy drive 22 . However, several recent simulations suggest that power-law spectra may still develop in the absence of a loss mechanism 26,27,36,55 . The set of conditions under which power-law spectra form in kinetic reconnection simulations remains an open issue.…”
Section: Discussionmentioning
confidence: 99%
“…While earlier numerical studies have identified multiple acceleration processes [9,[11][12][13][14]17], recent simulations have revealed an efficient nonthermal acceleration that gives hard powerlaw like energy distributions [16,18,19,[46][47][48][49]. In this paper, we summarize the relevant progress in this area.…”
Section: Introductionmentioning
confidence: 99%
“…case of an electron-positron plasma, which has been most widely explored in the literature, both in 2D (Zenitani and Hoshino 2001Zenitani and Hesse 2008;Jaroschek et al 2004Jaroschek et al , 2008Bessho and Bhattacharjee 2005, 2012Daughton and Karimabadi 2007;Lyubarsky and Liverts 2008;Cerutti et al 2012bCerutti et al , 2013Werner et al 2014) and in 3D (Zenitani and Hoshino 2008;Yin et al 2008;Liu et al 2011;Spitkovsky 2011a, 2012;Kagan et al 2013;Cerutti et al 2014b;Sironi and Spitkovsky 2014;Guo et al 2014). The physics of relativistic electron-proton reconnection, yet still at an early stage of investigation, shows remarkable similarities with electronpositron reconnection (Melzani et al 2014).…”
Section: Structure Of the Reconnection Layermentioning
confidence: 99%